Institutional evaluation: structures and processes of the nursing graduation course - José Paiva Abreu; Beatriz Guitton Oliveira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
This report is presented as a descriptive research with a quantitative nature approach and about studies of cases in education searching to evaluate the structures and the processes of a nursing graduation institution, from the view of the teaching staff and the students; to analyse the aspects which make difficult or easy the work/study of the people who are involved in that process and build institutional evaluation marks, according to the involved people's view.